Clinical assessment of inflammatory bowel disease activity: a critical overview - Fabisiak, Adam; Murawska, Natalia; Mokrowiecka, Anna; Małecka-Panas, Ewa; Fichna, Jakub (Journal of Medical Science, 2015)
Crohn’s disease (CD) and ulcerative colitis (UC), which belong to the group of inflammatory bowel diseases (IBD), are chronic inflammatory conditions of the gastrointestinal (GI) tract. Over the last eighty years the overview of IBD has evolved, along with disease symptom recognition, hypotheses on etiology and recommendations for clinical treatment. This review focuses on the clinical aspects of IBD throughout the years and discusses the most recent and future concepts in IBD diagnosis.